2019
DOI: 10.1088/1361-665x/ab2d39
|View full text |Cite
|
Sign up to set email alerts
|

Multiphysics methodology for thermal modelling and quantitative analysis of electromagnetic linear actuator

Abstract: Multiphysics methodology is a preferred tool for the design and optimization of electromagnetic linear actuators (EMLA). In this paper, a multiphysics method was proposed, which uses the non-simplified energy consumption distribution as the heat source for temperature field calculation, adjusts the material properties by temperature, and considers the interaction between motion (including impact) and loss. Then comprehensive experiments and quantitative analysis were carried out. The results show that the erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The plunger is driven by inputting the desired voltage for precise reciprocating action indirectly, and the flow is distributed based on the check valve train to achieve stable output flow. The schematic diagram of the EDDP is shown in figure 1 [32,33].…”
Section: The Operating Principle Of the Eddpmentioning
confidence: 99%
“…The plunger is driven by inputting the desired voltage for precise reciprocating action indirectly, and the flow is distributed based on the check valve train to achieve stable output flow. The schematic diagram of the EDDP is shown in figure 1 [32,33].…”
Section: The Operating Principle Of the Eddpmentioning
confidence: 99%
“…Therefore, many scholars have paid much attention to the Eddy effect and its influence on the dynamic response characteristics of the HSV. Zhao et al [26], Bai et al [27], and Tan et al [28] conducted numerical simulations to find that the Eddy effect has an important impact on the dynamic response of the HSV. Moreover, Zhao et al found that the Eddy effect exerts a greater influence on the actuation response time than the release response time for the conventional HSV.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the rapid development of smart materials, high magnetic energy rare earth permanent magnet materials, manufacturing technology, and advanced control theory. Scholars have further improved the performance of micro linear motors by using highly magnetic materials, designing Halbach arrays instead of conventional pole structures, as well as applying superconducting materials to make windings [6][7][8]. The electromagnetic linear actuators, as an important development direction of linear motors, have become a research hotspot for high-performance linear servo control due to the advantages of cogging-free torque, high linearity, simple structure, and convenient control compared to conventional permanent magnet synchronous linear motors [9,10].…”
Section: Introductionmentioning
confidence: 99%